Cutting-Edge Treatment of Unruptured Aneurysms - Vinall, Phil (MD Conference Express, 2010)
Although technical advances in the surgical management of aneurysms are limited, microsurgery can still be used to create elegant and anatomical bypasses in the hands of a skilled neurosurgeon. The evolving trends in the field include more minimally invasive approaches; more use of direct clipping, clip reconstruction, and bypass procedures; and less brain retraction and skull base surgery. Circulatory arrest as part of the aneurysm surgical process is no longer used.